Letting the solution define the problem: Canada’s COVID Alert app as a case of failed policy - Haggart, Blayne (Ineffective Policies, 2025)
Early in the global COVID-19 pandemic, smartphone-based apps were touted as a means to mitigate and even end the pandemic. The Canadian government debuted its contact notification app, the COVID Alert app, on 29 July 2020. As elsewhere, the app failed to live up to even modest expectations before being quietly retired on 17 June 2022. The COVID Alert app suffered an embrace of technological solutionism – defining a problem in terms of a preferred solution – and dataism, ‘the presumption that social reality can be fully captured by the collection of digital data’. Taken together, these ideologies short-circuited the policymaking process to focus more on the tech itself and the needs of the tech giants providing the digital infrastructure – Apple and Google – than on the nominal health-policy objective. In the end, failure was inevitable.